3D-functionalized carbon nanotube microsphere networks modified by 1-aminopyrene promote silicon anode with an enhanced cyclic performance for Li-ion batteries. (12th July 2022) - Liu, Wenjing; Hu, Yuxin; Zhou, Hanxiao; Li, Tianhui; Huang, Meiling; Qu, Meizhen; Peng, Gongchang; Xie, Zhengwei
Abstract: Although silicon has higher theoretical specific capacity to meet the demand for higher energy density, its large volume expansion and low conductivity make the practical application of silicon anode difficult in the field of lithium-ion batteries. In this work, Si@(AP-AOCNTs) composites with uniform conductive network and pore structure are prepared by spray drying method. In the composite microspheres, silicon particles are embedded into the 3D interwoven network of 1-aminopyrene modified oxidized carbon nanotubes, which can not only buffer the volume expansion of silicon, but also ensure the effective transport of electrons and ions. This is demonstrated by the remarkable cycle life, and the electrode still has a reversible specific capacity of 939.3mAh/g after 975 cycles at 0.5A/g. Moreover, 97.3% of the initial capacity (at 0.5A/g) is still retained after the rate cycling, when the current density returns to 0.5A/g. Graphical abstract: Image 1 Highlights: Three-dimensional carbon nanotube networks facilitate electron transport and particle integrity. 1-aminopyrene can effectively improve the dispersion uniformity of CNTs and favor the formation of a stable SEI film. Si@ (AP-AOCNTs) anode exhibits obvious improved rate and cyclic performance.